Sosialisasi Tanggap Bencana dan Pemulihan Pasca Bencana Bagi Masyarakat Desa Beruk Jatiyoso Karanganyar - Joko Pramono; Suwardi Suwardi (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
Beruk Village, located in Jatiyoso Subdistrict, Karanganyar Regency, Central Java, is classified as a high-risk area for landslides. This condition arises from its hilly topography and unstable soil structure, making the land susceptible to movement, particularly during periods of heavy rainfall. In recent years, landslide events have affected at least 70 families, particularly in Tasin Hamlet, which experienced severe destruction and, in some areas, complete ground leveling. These conditions indicate that landslide hazards in Beruk Village constitute a serious phenomenon requiring comprehensive attention and structured mitigation efforts. This community service program was designed to strengthen local preparedness through disaster awareness and capacity-building activities. The program employed two main approaches: delivering disaster mitigation material through lectures and conducting practical training facilitated by instructors from the Regional Disaster Management Agency (BPBD) of Karanganyar Regency, local community leaders, and village authorities. Evaluation results show that participants demonstrated high enthusiasm throughout the activities, indicating increased awareness of the importance of disaster-related knowledge and skills. Overall, this program contributed significantly to enhancing community readiness, improving disaster literacy, and promoting active participation in sustainable mitigation efforts.